Autophagy, apoptosis, vitamin D, and vitamin D receptor in hepatocellular carcinoma associated with hepatitis C virus. Issue 12 (March 2018) - Abdel-Mohsen, Mohamed Ahmed; El-Braky, Ahlam Abd-Allah; Ghazal, Abeer Abd El-Rahim; Shamseya, Mohammed Mohammed
Abstract : Abstract: The aims of this study were to investigate the interplay between autophagy and apoptosis and to investigate the association between both of autophagy and apoptosis and vitamin D and its receptor in hepatitis C virus (HCV) viral infection and its implication in the progression into hepatocellular carcinoma (HCC). A cross-sectional study where serum levels of microtubule-associated protein 1A/1B-light chain 3 (LC3); marker of autophagy, caspase-3; marker of apoptosis, vitamin D3 and vitamin D receptor (VDR) were measured in healthy subjects as well as HCV and HCV-HCC patients using enzyme-linked immunosorbent assay technique. Collectively, the liver profile revealed hepatic dysfunctions in HCV patients with or without HCC. A significant reduction in the serum concentration levels LC3 and caspase-3 were observed referring to the down regulation of autophagy and host-mediated apoptosis in HCV patients with or without HCC. Deficiency of vitamin D and decreased levels of its receptor were observed in HCV and HCV-HCC patients. The perturbation in vitamin D/VDR axis, which modulates both of autophagy and apoptosis in HCV infection, may point out to its involvement and implication in the pathogenesis of HCV infection and the development of HCV-related HCC. Therefore, supplementation with vitamin D may not be the only solution to restore the vital biological functions of vitamin D but VDR-targeted therapy may be of great importance in this respect.